AN OVERVIEW OF THE APPLICATION OF ORGANISATIONAL CITIZENSHIP BEHAVIOR (OCB) IN INDONESIA THROUGH A LITERATURE REVIEW - Ika Pratiwi; Martinus Tukiran; Rinsan Hutabarat; Jumadi Jumadi (International Journal of Economy, Education and Entrepreneurship, 2023)
Research on Organizational Citizenship Behavior (OCB) has progressed significantly in the West, resulting in a number of meta-analyses that helped standardise the concept and set the path for future studies. OCB research, on the other hand, has not been extensively investigated in the literature despite its popularity in Indonesia. The research method for writing this paper is a literature review; data search is carried out through three online journal databases that researchers can access (Google Scholar, Garuda Indonesia Portal and Science Direct). This search criterion is research conducted from 2018 to 2022 and the construct of “organisational citizenship behaviour” as a dependent variable. Several articles and findings are highlighted in the review of OCB research in Indonesia. 1) The unit of analysis for the research was white-collar workers; 2) most research methods utilised questionnaire analysis tools; and 3) data for two or more variables were derived from a single primary source, making the research susceptible to common method variance. The implication for the next OCB research is that it is necessary to review OCB specific to several companies or certain job characteristics. The research on personality in Indonesia must also involve a discussion of Indonesian state culture